Peranan Jaringan Sosial Pemerintah Kecamatan Sawangan Kabupaten Magelang dalam Pencegahan Stunting - Widiarti, Endang Retno; Purwanto, Danang; Zuhri, Saifuddin (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
The stunting rate in Magelang district reached 28.20% in 2022, requiring cooperation between stakeholders in handling the case. This research was conducted to examine the role of the Magelang district government s social network in preventing stunting. Qualitative research method with descriptive analytic approach was used by the researcher in studying the topic. The results showed that stunting is a complex problem so the district government formed a social network to prevent this problem from becoming more severe. The social network consists of several elements, namely PLKB Sawangan, Puskesmas, KUA, and GenRe Ambassadors. The social network formed is considered good based on Marx Granovetter s social network theory because it has norms, network density, embeddedness, and network holes so that stunting prevention efforts through this social network are effective. The role of the network is collectively implemented through the gothong sakcething program or the government movement in preventing stunting.